Diffusion tensor imaging and white matter abnormalities in patients with disorders of consciousness - Cavaliere, Carlo; Aiello, Marco; Di Perri, Carol; Fernandez-Espejo, Davinia; Owen, Adrian M.; Soddu, Andrea (Frontiers in Human Neuroscience, 2015)
Progress in neuroimaging has yielded new powerful tools which, potentially, can be applied to clinical populations, improve the diagnosis of neurological disorders and predict outcome. At present, the diagnosis of consciousness disorders is limited to subjective assessment and objective measurements of behaviour, with an emerging role for neuroimaging techniques. In this review we focus on white matter alterations measured using Diffusion Tensor Imaging on patients with consciousness disorders, examining the most common diffusion imaging acquisition protocols and considering the main issues related to diffusion imaging analyses. We conclude by considering some of the remaining challenges to overcome, the existing knowledge gaps and the potential role of neuroimaging in understanding the pathogenesis and clinical features of disorders of consciousness.